Getting to the Shore on Foot: Sustaining Harvester Access - Zoellick, Bill; Angione, Pauline; Farr, Emily; Fisher, Ada; Joyce, Jessica; Lauer, B; McMahan, Marissa; Pinkham, Michael; Rea, Vicki (Maine Policy Review, 2023)
"Working Waterfront" conjures images of the Portland Fish Exchange, Belfast shipyards, or wharves and piers in Stonington. Ensuring that such sites continue as essential elements of Maine’s marine economy is increasingly the focus of innovative action and policy development. But policies to address Maine’s working waterfronts must also attend to waterfront access required by those who reach it on foot. Such access rights are rarely conferred by private ownership. Instead, they depend on public ownership and, more frequently, on informal social arrangements between harvesters and property owners. In this article, we describe the nature of the shore access needed by on-foot harvesters, the contribution such harvesting makes to communities, and why walk-in access is disappearing. Drawing upon emerging initiatives by municipalities, nonprofit organizations, regional associations, and state government, we suggest actions and policies to help sustain on-foot waterfront access.